Transcriptional Effects of Glucocorticoid Receptors in the Dentate Gyrus Increase Anxiety-Related Behaviors - Sarrazin, Nadège (Public Library of Science, 2009)
The Glucocorticoid Receptor (GR) is a transcription factor ubiquitously expressed in the brain. Activation of brain GRs by high levels of glucocorticoid (GC) hormones modifies a large variety of physiological and pathological-related behaviors. Unfortunately the specific cellular targets of GR-mediated behavioral effects of GC are still largely unknown. To address this issue, we generated a mutated form of the GR called ΔGR. ΔGR is a constitutively transcriptionally active form of the GR that is localized in the nuclei and activates transcription without binding to glucocorticoids. Using the tetracycline-regulated system (Tet-OFF), we developed an inducible transgenic approach that allows the expression of the ΔGR in specific brain areas. We focused our study on a mouse line that expressed ΔGR almost selectively in the glutamatergic neurons of the dentate gyrus (DG) of the hippocampus. This restricted expression of the ΔGR increased anxiety-related behaviors without affecting other behaviors that could indirectly influence performance in anxiety-related tests. This behavioral phenotype was also associated with an up-regulation of the MAPK signaling pathway and Egr-1 protein in the DG. These findings identify glutamatergic neurons in the DG as one of the cellular substrate of stress-related pathologies.